槐花 물 추출물의 항염증 효과 - 배기상(Gi Sang Bae); 조범연(Beom Yeon Jo); 김민선(Min Sun Kim); 박경철(Kyoung Chel Park); 구본순(Bon Soon Koo); 서상완(Sang Wan Seo); 김성규(Sung Gyu Kim); 윤승원(Seung-Won Yun); 정원석(Won Seok Jung); 함경완(Kyung Wan Ham); 송호준(Ho Joon Song); 윤명자(Myung Ja Youn); et al. (동의생리병리학회지, 2009)
The purpose of this study was to investigate the anti-inflammatory effects of aqueous extract from Sophora Japonica (SJ) on the RAW 264.7 cells. To evaluate the anti-inflammatory effects of SJ, we examined the cytokine productions including nitric oxide (NO), interleukin (IL)-1b, IL-6 and tumor necrosis factor-a (TNF-a) in lipopolysaccharide (LPS)-induced RAW 264.7 cells and also inhibitory mechanisms such as mitogen-activated protein kinases (MAPKs) and nuclear factor kappa b (NF-kB) using Western blot. SJ inhibited LPS-induced production of NO, TNF-a but not of IL-1b and IL-6 in RAW 264.7 cells. SJ inhibited the activation of MAPKs such as extracelluar signal-regulated kinase (ERK 1/2), c-Jun NH2-terminal kinase (JNK) and p38 but not of NF-kB in the LPS-stimulated RAW 264.7 cells. In conclusion, SJ down-regulated LPS-induced NO and TNF-a productions via MAPKs, which could be a clinical basis for inflammatory diseases and autoimmune diseases. The purpose of this study was to investigate the anti-inflammatory effects of aqueous extract from Sophora Japonica (SJ) on the RAW 264.7 cells. To evaluate the anti-inflammatory effects of SJ, we examined the cytokine productions including nitric oxide (NO), interleukin (IL)-1b, IL-6 and tumor necrosis factor-a (TNF-a) in lipopolysaccharide (LPS)-induced RAW 264.7 cells and also inhibitory mechanisms such as mitogen-activated protein kinases (MAPKs) and nuclear factor kappa b (NF-kB) using Western blot. SJ inhibited LPS-induced production of NO, TNF-a but not of IL-1b and IL-6 in RAW 264.7 cells. SJ inhibited the activation of MAPKs such as extracelluar signal-regulated kinase (ERK 1/2), c-Jun NH2-terminal kinase (JNK) and p38 but not of NF-kB in the LPS-stimulated RAW 264.7 cells. In conclusion, SJ down-regulated LPS-induced NO and TNF-a productions via MAPKs, which could be a clinical basis for inflammatory diseases and autoimmune diseases. KCI Citation Count: 2